Potencial de genótipos de canola (Brassica napus L. var. oleifera) na supressão de plantas daninhas - Rizzardi, Aline (2007)
Alellophaty is a natural phenomenon among plants and its characterized by the production of chemical substances released in the environment. Several plants, including the cultivated species, have the capability to suppress other plant growth, although the mechanisms of growth suppression are frequently unknown, which makes not feasible its use in the management of harmful plants. Canola produces several alellopathic compounds that influence the germination and the development of plants growing around it. The objective of this work was to evaluate the alellophatic potential of canola (Brassica napus L. var. oleifera) genotypes. Three experiments were carried out at the Center of Extension and Farming Research and at the Center of Food Research of the University of Passo Fundo. The first experiment evaluated the effects of canola aqueous extract on achene germination and length of seminal roots of hairy beggartick (Bidens pilosa L.). Thirteen canola genotypes and five concentrations of extract were tested (100%, 75%, 50%, 25% and 0%). The canola extracts negatively influenced achene germination and root growth, although low extract concentrations stimulated the same processes. Overall, there were few differences among genotypes in their capability to inhibit germination and seminal root growth. Differences among them were detected only at low extract concentrations. In the second experiment, with chromatographic analysis of canola genotypes, the resulting profiles were similar, indicating the genotypes did not differ in production of chemicals. In a third experiment, weed suppression and the yield of soybean sown in succession to canola (genotypes Hyola 43, 401 Hyola and Hyola 420), black oat (Avena strigosa Schreb) residues and a check without straw were evaluated. Canola inhibited Xanthium strumarium L and reduced the population of soybean plants, but there were no differences in soybean yield and its components from the other treatments. Therefore, the preceding crop of canola had no negative effect on the yield of following soybean crop